Napalm and After: The Politics of Grace Paley's Short Fiction - Newman, Judie (Modern Humanitites Research Association, 2001)
Comparatively few contemporary writers have accompanied American POWs home from Hanoi, been arrested on the White House Lawn, or been dragged off in shackles to serve time in the Greenwich Village Women's House of Detention. Paley's pacifist, socialist politics are also deeply rooted in a family past where memories were still fresh of Tsarist oppression - one uncle shot dead carrying the red flag, and parents who reached America only because the Tsar had a son and amnestied all political prisoners under the age of twenty-one. At this point, Paley's father (imprisoned in Archangel) and her mother (in exile) took their chances (and all their surviving relatives) and very sensibly ran for their lives. Her grandmother recalled family arguments around the table between Paley's father (Socialist), Uncle Grisha (Communist), Aunt Luba (Zionist), and Aunt Mira (also Communist). Paley's own street-wise adolescence involved the usual teenage gang fights, between adherents of the Third and Fourth Internationals.